2011
DOI: 10.5146/tjpath.2011.01043
|View full text |Cite
|
Sign up to set email alerts
|

Profile of gallbladder diseases diagnosed at afyon kocatepe university: a retrospective study

Abstract: Objective: Superficial tumors including Ta, Tis, and T1 make up 75% of urothelial carcinomas of the bladder. While the behavior of these superficial urothelial cancers is relatively benign, invasive tumors have a significant mortality rate. However, Ta and T1 tumors might display different biological behavior. There is therefore a great need for biomarkers that can accurately distinguish the behavior of urothelial carcinomas in addition to tumor grade and stage. our aim was to determine the immunohistochemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
(20 reference statements)
1
0
0
Order By: Relevance
“…10 The data from the present study support these findings. Cholesterol stones are the most common type of gallstones, and they have been identified as 67.5% of gallstones by Mazlum et al 11 , 70% by Van Erpecum, 3 and 75% by Whiting et al 5 Similarly, we found that 58.7% of the sample gallstones were cholesterol stones. Otherwise, the mean gallstone cholesterol concentration was reported to be 25% by Angwafo et al 12 59.7% by Chandran et al 9 and 60.8% by Jaraari et al 13 We determined that the mean stone cholesterol concentration was 52.1%.…”
Section: Discussionsupporting
confidence: 68%
“…10 The data from the present study support these findings. Cholesterol stones are the most common type of gallstones, and they have been identified as 67.5% of gallstones by Mazlum et al 11 , 70% by Van Erpecum, 3 and 75% by Whiting et al 5 Similarly, we found that 58.7% of the sample gallstones were cholesterol stones. Otherwise, the mean gallstone cholesterol concentration was reported to be 25% by Angwafo et al 12 59.7% by Chandran et al 9 and 60.8% by Jaraari et al 13 We determined that the mean stone cholesterol concentration was 52.1%.…”
Section: Discussionsupporting
confidence: 68%